Dynamic business law : (McGraw Hill, 2013)
Dynamic Business Law Summarized Cases is appropriate for the two term business law course; Emphasis on the BUSINESS in business law. Dynamic Business Law emphasizes the tie of legal issues back to the core business curriculum; Emphasis on TEACHING Dynamic Business Law contains a helpful instructor’s manual, particularly for the many adjuncts teaching this course; Emphasis on Critical Thinking